Geological factors controlling high flowback rates of shale gas wells in the Changning area of the southern Sichuan Basin, China - Liu, Yongyang; Zhao, Shengxian; Yang, Xuefeng; Li, Bo; Zhang, Jian; Ji, Chunhai; Huang, Shan; Wu, Tianpeng; Qu, Chongjiu (Frontiers in Earth Science, 2024)
In the Changning block of the southern Sichuan Basin, the shale gas wells in the Upper Ordovician Wufeng Formation to Lower Silurian Longmaxi Formation (Wufeng-Longmaxi) demonstrate significant difference in flowback rate of fracturing fluid, given the same fracturing scale and production time. Based on the P90 curve of flowback rate with time, wells with high flowback rates in this area are categorized, and they are generally defined with the 100-day flowback rate of ˃40%, the 200-day flowback rate of ˃50%, and the first-year flowback rate ˃60%. Through comprehensive research on the geological characteristics of the Changning block, the geological factors that cause high gas well backflow rates have been identified. The results are obtained in four aspects. First, gas wells with high flowback rates generally show higher flow rates for smaller distances to the fault, and the NE faults formed during the late Yanshanian to early Himalayan and with fault throw ˃200 m have the greatest impact on the flowback rate. Second, plane heterogeneity of water saturation contributes to the high flowback rate of some wells. Third, the proportion of the Middle Ordovician Baota Formation in the horizontal section of wells is positively related to the flowback rate, and the drilling and fracturing of the Baota limestone with high water content can lead to high flowback rates of gas wells to some extent. Fourth, unidirectional linear natural fractures between wells can easily cause inter-well frac-hit, leading to high flowback rates of gas wells. In conclusion, the research results are helpful in predicting areas where high backflow rate gas wells may occur and developing corresponding drainage and production methods in advance.